Brain ethanolamine phospholipids, neuropathology and cognition: A comparative post-mortem analysis of structurally specific plasmalogen and phosphatidyl species - Goodenowe, Dayan B.; Senanayake, Vijitha (Frontiers in Cell and Developmental Biology, 2022)
Reduced cognition in the elderly is associated with low levels of plasmalogens and high levels of lipid rafts, amyloid plaques, and neurofibrillary tangles in the brain. A systematic integrative analysis of key indices of these pathologies to determine their collective and independent contributions to cognition was performed. Levels of four phosphatidylethanolamines (PE) and four ethanolamine plasmalogens (PL) of identical sn-1 carbon length and desaturation (stearic, 18:0) and identical sn-2 fatty acid compositions of varying side chain lengths and degrees of unsaturation (oleic, 18:1; linoleic, 18:2; arachidonic, 20:4; docosahexaenoic, 22:6), flotillin-1 expression and amyloid plaque and neurofibrillary tangle densities were measured in inferior temporal cortex (ITC) tissue from 100 elderly subjects (Rush University Memory and Aging Project, 88.5±5.8 years old). Subjects were evenly distributed with respect to gender (52/48, F/M) and cognitive status (38/24/38, no cognitive impairment/mild cognitive impairment/Alzheimer’s dementia) proximate to death. Multivariate logistic regression analyses were used to determine the relative and collective associations of the neuropathological indices with cognition. Higher levels tangles, amyloid, or flotillin and lower levels of PL 18:0/22:6 were significantly associated with lower cognition in the base model (adjusted for age, sex, education). Multivariate analysis revealed that only PL 18:0/22:6 (β= 0.506; p< 0.00001), tangles (-0.307; p<0.01), and flotillin (-0.2027; p<0.05) were independently associated with reduced cognition. PL 18:0/22:6 and PE 18:0/22:6 levels were independently associated with cognition in the presence of tangles, amyloid, and flotillin, but only PL 18:0/22:6 retained its association when both PL and PE 18:0/22:6 were included in the model indicating that PE 18:0/22:6 levels were associated with PL 18:0/22:6, not cognition. Only high brain levels of PL 18:0/22:6 (>mean+1SD) was predictive of normal cognition (coef = 1.67, p<0.05) and non-demented state (coef = -2.73, p<0.001), whereas low levels of PL 18:0/22:6 and high levels of tangles or flotillin were predictive of dementia. The association of high brain polyunsaturated (PUFA)-PL levels with better cognition was independent of amyloid plaque, neurofibrillary tangle, PE, and flotillin-1 expression. Maintenance or augmentation of brain docosahexaenoic (DHA)-PL levels warrants further investigation as a target for preventing cognitive decline or improving cognition in the elderly, respectively.